The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1007/bf00058828
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of aliphatic hydrocarbon-degrading microorganisms

Abstract: This paper reviews aspects of the physiology and biochemistry of the microbial biodegradation of alkanes larger than methane, alkenes and alkynes with particular emphasis upon recent developments. Subject areas discussed include: substrate uptake; metabolic pathways for alkenes and straight and branched-chain alkanes; the genetics and regulation of pathways; co-oxidation of aliphatic hydrocarbons; the potential for anaerobic aliphatic hydrocarbon degradation; the potential deployment of aliphatic hydrocarbon-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(64 citation statements)
references
References 67 publications
1
63
0
Order By: Relevance
“…In this pathway, the reaction proceeds as follows: alkanes are first attacked at their terminal methyl group to yield the corresponding primary alcohols, which are further oxidized by alcohol dehydrogenases and aldehyde dehydrogenases to fatty acids. The fatty acids then enter β-oxidation (Watkinson and Morgan, 1990). Second is biterminal oxidation, in which the termini of the n -alkane undergo oxidation to the corresponding fatty acid without rupturing of the carbon chain.…”
Section: N-alkane Degradation Pathwaymentioning
confidence: 99%
“…In this pathway, the reaction proceeds as follows: alkanes are first attacked at their terminal methyl group to yield the corresponding primary alcohols, which are further oxidized by alcohol dehydrogenases and aldehyde dehydrogenases to fatty acids. The fatty acids then enter β-oxidation (Watkinson and Morgan, 1990). Second is biterminal oxidation, in which the termini of the n -alkane undergo oxidation to the corresponding fatty acid without rupturing of the carbon chain.…”
Section: N-alkane Degradation Pathwaymentioning
confidence: 99%
“…In A. hongdengensis A-11-3, we recently found that pristane selectively activates the expression of alkB1 , P450-3 and almA (Wang and Shao, 2012a). However, the metabolic pathways that mediate this activity are poorly understood, although they may involve the ω- or β-oxidation of the hydrocarbon molecule (Watkinson and Morgan, 1990). …”
Section: Degradation Pathways Of N-alkanesmentioning
confidence: 99%
“…1E). Hydrocarbon degradation starts with three terminal oxidation steps to the corresponding alcohol, aldehyde, and acid, involving a monooxygenase, alcohol dehydrogenase, and aldehyde dehydrogenase (34). These reactions take place outside the cyto-plasm to avoid toxicity of the aldehyde intermediates.…”
Section: Twin-arginine Motif and Secretion Of Overexpressed Phospholimentioning
confidence: 99%